Students’ Perceptions on Online Peer Feedback Practice In EFL Writing - I Gede Krisna Meialldy Putra; Made Hery Santosa; Ni Putu Astiti Pratiwi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
ABSTRACTThis study investigated the implementation of online peer feedback practice, the students’ perceptions toward online peer feedback practice, and the students’ challenges toward online peer feedback practice. The study employed a mixed-method design with SMA PGRI Blahbatuh students as the population, while the sample was 132 students. The data were collected through observing the online classes using an observation checklist, conducting a survey using a questionnaire, and conducting an interview using an interview guide through focus group discussion. The study’s findings imply several strengths and weaknesses in the online peer feedback practice. It was also revealed that the students had positive perceptions toward the online peer feedback practice. Meanwhile, the interview results revealed several contradictory results regarding the students’ challenges. The students preferred the teacher’s feedback after the practice since it would make them feel safe. The students also suggested anonymous peer feedback practice since they could give the comments honestly, with details, and specifics. Through this study, students can learn to improve their skills in communicating and collaborating with their peers. The study also provided the teacher information to create more effective and efficient online peer feedback practice. ABSTRAKPenelitian ini didesain untuk menyelidiki penerapan praktik umpan balik rekan secara daring, persepsi siswa terhadap praktik umpan balik rekan secara daring, dan tantangan siswa terhadap praktik umpan balik rekan secara daring. Penelitian ini menggunakan desain kombinasi dengan siswa SMA PGRI Blahbatuh sebagai populasi, sedangkan sampelnya hanya 132 siswa. Pengumpulan data dilakukan melalui observasi kelas online menggunakan lembar observasi, survei menggunakan kuesioner, dan wawancara menggunakan pedoman wawancara melalui diskusi kelompok terfokus. Temuan penelitian menyiratkan bahwa ada beberapa kekuatan dan kelemahan dalam praktik umpan balik rekan secara daring. Terungkap pula bahwa siswa memiliki persepsi positif terhadap praktik umpan balik rekan secara daring. Sementara itu, hasil wawancara mengungkapkan beberapa hasil yang kontradiktif terkait tantangan siswa. Siswa lebih menyukai masukan dari guru setelah latihan karena akan membuat mereka merasa lebih aman. Para siswa juga menyarankan praktik umpan balik rekan anonim karena mereka dapat memberikan komentar dengan jujur, dengan detail, dan spesifik. Melalui penelitian ini, siswa dapat belajar meningkatkan keterampilannya dalam berkomunikasi dan berkolaborasi dengan teman sebayanya. Penelitian ini juga memberikan informasi kepada guru untuk menciptakan praktik umpan balik teman secara daring yang lebih efektif dan efisien.